Design and Development of Affordable Salted Fish Drying Machine - NADARAJAH, VSHNU; Dr.Mohd Fahrul Bin Hassan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This paper presents the development and testing of a prototype saltedfish drying machine aimed at enhancing the efficiency and productivityof Small and Medium Industries (SMIs) involved in fish drying. Theresearch encompasses the design, fabrication, and comprehensivetesting of the prototype. Performance testing demonstrated significantimprovements in drying efficiency and product consistency. This studycontributes to the advancement of food processing technology byproviding a reliable solution for the fish drying industry.